ANALISIS VEGETASI PADA TEGAKAN YANG TERINVASI AKASIA (Acacia nilotica) DI TAMAN NASIONAL BALURAN, JAWA TIMUR - Djufri (LPPM Universitas Terbuka, 2006)
The research was done in Baluran National Park, Banyuwangi East Java in April until June 2004. The objectives of this research are: to determine species composition, importance value of species, diversity index and evenness index, similarity index, and distribution pattern of species. This research used quadratic method. The determination of the species distribution was calculated using Poisson distribution formula and classification of community using similarity index formula and cluster analysis. The results of this research indicated that, there were 63 species of plants including 18 families. The importance value was between 0,97-42,58, the diversity index was between 1,1504-2,7556 and evenness index was between 1,1067-1,7854. The result of classification community indicated that savanna Baluran National Park can be devided into three groups (a). Open savanna no A. nilotica stand, (b).savanna with density of A. nilotica stand 1500-3000 individuals/ha, and (c).savanna with dense A. nilotica stand > 3000 individuals/ha.